The Relationship Between Self-Efficacy and Reflective Practices of Pre-service English Teacher in Indonesian EFL Context - Harahap, Mukhni Rahma Wati; Fithriani, Rahmah (Universitas Lancang Kuning, 2024)
Reflective practice has become an issue that has been widely researched, but very few have linked it to pre-service teacher self-efficacy, especially in the Indonesian context. Despite the Ministry of Education’s advocacy for reflective practices as an expected competency, Indonesian teachers have relatively low awareness of the concept and even fewer truly implement the practice. This study is intended to investigate the relationship between EFL pre-service English teachers’ self-efficacy and reflective practices. The quantitative method was chosen since the researchers intended to find out whether there is a significant relationship between pre-service teachers’ self-efficacy and reflective practices with computed by SPSS 23. There are 15 pre-service English teachers of UINSU as the sample and there are 8 items in this study. Researchers used 5 point Likert scale. Simple random sampling was technique to gain the data. The result of data analysis reflected that the null hypothesis (Ho) is rejected. It means that the teachers’ self-efficacy and reflective practices has significant relationship that marked on sig. value is 0.01 is below than 0.05 with level of relationship moderate (0.884). This research contributes to increasing practioners’ awareness of reflective practices and has a significant effect on pre-service English teachers to understand the role of self-efficacy and reflective practice better before teaching English as a Foreign Language (EFL) to their students. The results support that reflective practice can make pre-service English teachers achieve and maintain their professionality English teachers in their career.